Gecko‐Gaskets for Multilayer, Complex, and Stretchable Liquid Metal Microwave Circuits and Antennas. Issue 11 (20th September 2017) - Zandvakili, Mersedeh; Honari, Mohammad Mahdi; Mousavi, Pedram; Sameoto, Dan
Abstract: This paper describes a reliable, repeatable, and cost effective solution for fabrication of complex mechanically reconfigurable microfluidic devices for soft electronics. The devices are made of eutectic gallium indium (EGaIn) in styrene‐ethylene‐butylene‐styrene thermoplastic elastomer with gecko‐adhesive based bonding which both aids in sealing thin channels and directing flow of high surface energy metal into small channels in a repeatable process. Selective filling of complex microfluidic structures is achieved by controlled advancement of EGaIn‐air interface using optimized hydrophobic valves. These valves are designed based on EGaIn's critical Laplace pressure to fabricate variable aspect ratio and multilayer features or designs with multiple branches and arrays of isolated elements. As a proof of concept, different antennas (bow‐tie, folded and multilayer dipoles, and microstrip patch antennas) and a hybrid power divider are fabricated with total device thicknesses less than 600 µm. These devices can conform to complex surfaces for applications like body worn sensors, and can be stretched or bent to change their electromagnetic properties such as center frequency, bandwidth, and impedance matching. Abstract : Reversibly bonded gecko adhesive gaskets are employed to seal microfluidics for injection of liquid metal. The gecko adhesive fibers act to both seal channels and direct the flow of high surface tension liquid metal alloys into complex planar and multilayer shapes with a single injection molding step. Reconfigurable complex and flexible antennas are demonstrated with this process.